PENINGKATAN PRODUKTIVITAS PENGERAJINANYAMAN SURYA PALM DAN CAHAYA PALM - Pandawani, Ni Putu; Parwita, Gde Bayu Surya; Paramita D., Putu Ayu (Forum Layanan IPTEKS Bagi Masyarakat (FLipMAS) Wilayah Bali, 2018)
UD. Surya Palm is about 20 km to the east of Denpasar, namely in Banjar Kertiyasa, Bona Village, Blahbatuh District, Gianyar Regency, Bali. UD. UD. Surya Palm as a program partner SME is a small business engaged in crafting a variety of woven ornaments with the main raw material of mendong rope with woven models produced including lamp ornaments, model ornaments in various forms namely the shape of dogs, giraffes, horses, pigs and elephants. Palm Light is 23 km to the east of Denpasar, namely in the Banjar Pasedana, Bona Village, Blahbatuh District, Gianyar Regency, Bali. UD. Cahaya Palm as a program partner SME is a small business engaged in the craft of various woven bags and wallets with the main raw materials of palm leaves and pandanus. The second product of the UKM has not only been marketed in Bali and Java, but has also become an export commodity to the destination countries, namely the Netherlands, Australia, Britain, Japan and Hawaii.The problems faced in developing handicrafts are very varied starting from human resources and competencies of craftsmen, technology, marketing, capital, including sources of raw materials,